Purification, crystallization and preliminary X‐ray crystallographic analysis of human IL‐18 and its extracellular complexes. Issue 10 (1st October 2014) - Kimura, Takeshi; Tsutsumi, Naotaka; Arita, Kyohei; Ariyoshi, Mariko; Ohnishi, Hidenori; Kondo, Naomi; Shirakawa, Masahiro; Kato, Zenichiro; Tochio, Hidehito
<x xml:space="preserve">Abstract</x> Interleukin‐18 (IL‐18), a pro‐inflammatory cytokine belonging to the interleukin‐1 (IL‐1) family, is involved in the pathogenesis of autoimmune/autoinflammatory and allergic diseases such as juvenile idiopathic arthritis and bronchial asthma. IL‐18 forms a signalling complex with the IL‐18 receptor α (IL‐18Rα) and β (IL‐18Rβ) chains; however, the detailed activation mechanism remains unclear. Here, the IL‐18–IL‐18Rα binary and IL‐18–IL‐18Rα–IL‐18Rβ ternary complexes were purified and crystallized as well as IL‐18 alone. An X‐ray diffraction data set for IL‐18 was collected to 2.33 Å resolution from a crystal belonging to space group P21, with unit‐cell parameters a = 68.15, b = 79.51, c = 73.46 Å, β = 100.97°. Crystals of both the IL‐18 binary and ternary complexes belonging to the orthorhombic space groups P21212 and P212121, respectively, diffracted to 3.10 Å resolution. Unit‐cell parameters were determined as a = 135.49, b = 174.81, c = 183.40 Å for the binary complex and a = 72.56, b = 111.56, c = 134.57 Å for the ternary complex.